Japura Pilot Academy Dengan Pendekatan Arsitektur Metafora - Lupita Lupita; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Lack of source needs experts in aviation in Indonesia, especially in Indragiri Hulu Regency, Riau becoming a problem in the world of transportation. Provision of aviation facilities must be supported by a reliable human resources and competent in their fields. Flight school to become a facility to produce reliable human resources and competently, especially in the field of aviation in particular Department of the Pilot. In the design of aviation high school needs to be seen applying the concepts and themes. So the design approach will use the architecture of a Tangible Metaphor will apply the shapes of Dragonfly, so people can identify the function of building just by looking at the physical appearance of the building and generate a more modern formations. Produce a more expressive architecture by trying to move the information from the subject to the building. The result was the Japura Pilot Academy will implement a Dragonfly into buildings.Keywords: Pilot, Aviation High School, Metaphore Architecture